Validation of Pharmacogenetic Testing Before Initiation of Warfarin Therapy - Chowdhury, MSI Tipu; Khaled, Md Fakhrul Islam; Sultana, Sadia; Rahman, Mohammad Walidur; Mandal, MRM; Ahmed, Khurshed; Hoque, Harisul (University Heart Journal, 2019)
Warfarin is an oral anticoagulant used to prevent or treat clotting disorders associated with venous thrombosis, pulmonary embolism, atrial fibrilation, cardiac valve replacement, stroke and acute myocardial infarction. It is a vitamin K antagonist composed of S- and R- isomers. The more potent S-warfarin is metabolized by cytochrome 450 isoenzyme 2C9 (CYP2C9), encoded by CYP2C9 gene. Warfarin exerts its anticoagulants effect by inhibitingits target enzyme vitamin K epoxide reductase (VKOR), encoded by vitamin K epoxide reductase subunit 1 (VKOR1) gene. Genetic variation in the CYP2C9 and VKOR1 gene can affect warfarin efficacy and dose required to achieve stable International Normalization Ratio (INR). Specifically two variants in the CYP2CP gene (CYP2C9*2 and CYP2C9*3) result in an enzyme with reduced activity, leading to increased active warfarin levels. A variant in the VKORC1 gene (VKORC1-1639 G>A) can lead to reduced gene expression resulting in decresed level of VKOR. Together these three variants can account for 40-70% of the variability of warfarin dose. Carriers of variant alleles are at higher risk for bleeding complications, particularly at the induction of warfarin therapy. So, genotype-guided dosing algorithms would be better approximate for maintenance of warfarin dose than fixed-dose algorithms. University Heart Journal Vol. 15, No. 2, Jul 2019; 74-78